The Role of Virtual Leadership to Improve Learning Organizations in Industry 4.0 - Joyada Siallagan, Ari Saptono, Ma’ruf Akbar, Emilkamayana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To be able to achieve the goals of organizational success requires leaders who are not only able to carry out management functions such as planning, organizing, directing, and supervising an organization. But the leader here has a very crucial role, especially in the development of industry 4.0. The development of industry 4.0 itself prioritizes technology based on maximum speed and efficiency. Where traditionally, the leader is always there when in the company in controlling and overseeing his subordinates. However, sometimes challenges occur because the leader is not always in place. It is a challenge for the company, so that with this virtual leadership, it is expected to be an opportunity to improve the company's progress following industry 4.0 adoption. Hence, virtual leadership becomes a competitive advantage for the company's progress, especially for the development of learning organizations in the company. That is why this article will discuss the role of Virtual Leadership to realize Learning Organizations in the Industrial Age 4.0. This paper used qualitative methods by reviewing and synthesizing journals related to Virtual Leadership and Learning Organizations. Virtual leadership in learning organizations requires something more. In learning organizations, managers learn to think about 'control with' rather than 'control' of others. Because the term Industry 4.0 continues to gain strength. The presence of industry 4.0 will make it easier for virtual leaders to improve digital manufacturing drives and create other business profits in the company.